Immunoassay : a survey of patents, patent applications, and other literature, 1980-1991 - Sigmond, J.; Salomons, Bernard; Terpstra, Marten (Elsevier Applied Science, 1992)
This book presents the results of a comprehensive study of literature on patents, patent applications and other literature, such as journal articles. The survey covers literature published from the United States, Japan and Western Europe between January 1980 and April 1991.